PENGETAHUAN MAHASISWA KEPERAWATAN TENTANG SASARAN KESELAMATAN PASIEN: Undergraduate Nursing Students Knowledge about Patient Safety Goals - Aprilia Nuryanti (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2019)
The people’s demands for service satisfaction and patient safety during care were a major challenge for the world of nursing. Students must be equipped with adequate knowledge, attitudes and skills in implementing the patient safety goals program. The purpose of this study was evaluate the knowledge and learning experience of students towards Patient Safety Goals (PSG). Descriptive research was conducted on 71 level II students who had obtained patient safety subject chosen by convenient sampling technique. The questionnaire was used to measure the level of knowledge about PSG. The FGD was conducted on 7 participants to explore lecture in class and laboratory practice experiences. Student knowledge about patient safety goals rated category fairly by 53,5% of the samples. Good level of knowledge on patient safety goals 4. Lecturers are expected to emphasize the interests of patient safety goals when teaching subjects related to patient and family services. It is necessary to develop patient safety goals learning outcomes with practicum methods and adjust the development of patient safety goals instruments in the practice area.